The Influence of Agile Leadership and Organizational Culture on Organizational Citizenship Behavior of Civil Servants at the Alianyang Health Center in Pontianak City - Ramadhani, Wirayudha; Yasmin, Devi (UNIVERSITAS PAKUAN, 2025)
This study aims to examine the impact of Agile Leadership and Organizational Culture on Organizational Citizenship Behavior at Alianyang Health Center. Using an associative quantitative approach, the study involves 38 respondents selected via total sampling. The data collection methods include instrument validation and reliability tests, classical assumption tests (normality, linearity, and multicollinearity tests), and hypothesis testing with multiple linear regression, correlation coefficient (R), coefficient of determination (R²), simultaneous tests, and partial tests. The multiple regression analysis yields the equation Y = 1.811 + 0.297 X1 + 0.307 X2. The correlation coefficient of 0.678 indicates a strong relationship between Agile Leadership, Organizational Culture, and Organizational Citizenship Behavior. The coefficient of determination reveals that 46% of the variation in Organizational Citizenship Behavior is influenced by Agile Leadership and Organizational Culture, while 54% is attributed to other factors not covered in the study. Simultaneous testing shows a significant impact (F = 14.998 F table = 3.27), confirming that both Agile Leadership and Organizational Culture significantly affect Organizational Citizenship Behavior. The partial test for Agile Leadership (p = 0.002 0.05) and Organizational Culture (p = 0.003 0.05) indicates significant effects on Organizational Citizenship Behavior.